1991
DOI: 10.1128/iai.59.10.3472-3477.1991
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of individual toxin components to virulence of Bacillus anthracis

Abstract: Three proteins, protective antigen (PA), lethal factor (LF), and edema factor (EF; a calmodulin-dependent adenylate cyclase), compose the lethal (PA+LF) and edema (PA+EF) toxins secreted by Bacillus anthracis. Mutant strains, each deficient in the production of one toxin component, were constructed, and their virulence was then studied. A kanamycin resistance cassette was inserted in each cya (encoding EF) and lef(encoding LF) gene, and the constructs were separately introduced into B. anthracis Sterne on a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(148 citation statements)
references
References 34 publications
(38 reference statements)
5
142
0
1
Order By: Relevance
“…4A, region highlighted in magenta). This domain is usually characteristic for the B subunits of binary AB toxins, like C. botulinum C2 toxin component-II (Kimura et al, 1998), C. difficile binary toxin B (cdtB) (Stubbs et al, 2000), C. perfringens iota toxin (Perelle et al, 1993), and B. anthracis anthrax toxin PA component (Welkos et al, 1988;Pezard et al, 1991), but it has also been identified in Plx2B (Fünfhaus et al, 2013), the B subunit belonging to the C3-like toxin Plx2A of P. larvae ERIC I (Fünfhaus et al, 2013;Ebeling et al, 2017). In addition, we detected a 124-residue carbohydrate binding domain of the CBM_4_9 superfamily (acc.…”
Section: Resultsmentioning
confidence: 99%
“…4A, region highlighted in magenta). This domain is usually characteristic for the B subunits of binary AB toxins, like C. botulinum C2 toxin component-II (Kimura et al, 1998), C. difficile binary toxin B (cdtB) (Stubbs et al, 2000), C. perfringens iota toxin (Perelle et al, 1993), and B. anthracis anthrax toxin PA component (Welkos et al, 1988;Pezard et al, 1991), but it has also been identified in Plx2B (Fünfhaus et al, 2013), the B subunit belonging to the C3-like toxin Plx2A of P. larvae ERIC I (Fünfhaus et al, 2013;Ebeling et al, 2017). In addition, we detected a 124-residue carbohydrate binding domain of the CBM_4_9 superfamily (acc.…”
Section: Resultsmentioning
confidence: 99%
“…Intradermal injections of PA + EF (or oedema toxin, ET) induce oedema in the skin (Stanley and Smith, 1961), and may also be lethal. The role of toxins in strain virulence in vivo has been demonstrated by gene deletion, showing a synergic effect of EF and LF (Pezard et al, 1991). Crystal structures have been obtained for all three components of these toxins (Petosa et al, 1997;Pannifer et al, 2001;Drum et al, 2002).…”
Section: The Molecular Characterization Of Lethal and Oedema Toxin Efmentioning
confidence: 99%
“…EF produces an increase in the intracellular level of cyclic-AMP through its calcium/calmodulin-dependent adenylate cyclase activity (Moayeri and Leppla, 2004). Deletion of EF or LF leads to a 10-and 1000-fold attenuation of bacterial virulence respectively (Pezard et al, 1991).…”
Section: Introductionmentioning
confidence: 99%